Pengaruh Letak Posisi Eksplan dan Sitokinin Pada Perkecambahan Biji Manggis (Garcinia mangostana L.) Lokal Aceh Secara in-Vitro - Handayani, Rd Selvy; Maisura, Maisura; Rizki, Astia (Faculty of Agriculture, Universitas Malikussaleh, 2017)
The application of modern biotechnology is needed in order to enhance the genetic diversity of mangosteens. The application of tissue culture on mangosteens is an important thing to do to support the biotechnology program of mangosteen plants. The purpose of this research is to reveal the influence of location of explants and Benzylaminopurine (BAP) concentration on germination of local Acehnese mangosteens in vitro. This research was conducted at the Laboratory of tissue culture of the Faculty of Agriculture, Malikussaleh University from March to May 2017. The study used an environmental design in the form of Completely Randomized Design (CRD) with two factors. The first factor is the location of explant position is abaxial (L1) and adaxial (L2). The second factor was the concentration of BAP 0 mg / L (B0), 2.5 mg / L (b1), and 5 mg / L (B2). The results showed that the position of eksplan gave an effect on mangosteen germination in vitro for its shoot length variables. The explant positions that had the best effect on the growth of in vitro mangosteen sprouts were adaxial. BAP concentration had an effect on germination of mangosteen in vitro for its bud growth and life percentage. 2.5 ppm of BAP concentration was the best concentration for mangosteen seed growth in vitro. There was no interaction between eksplan position and BAP concentration in all observed variables